Multistage A-O Activated Sludge Process for Paraformaldehyde Wastewater Treatment and Microbial Community Structure Analysis. (13th November 2016) - Zheng, Danyang; Sun, Yujiao; Li, Huijuan; Lu, Sidan; Shan, Mingjun; Xu, Shangwei
Abstract : In recent years, the effect of formaldehyde on microorganisms and body had become a global public health issue. The multistage combination of anaerobic and aerobic process was adopted to treat paraformaldehyde wastewater. Microbial community structure in different reaction stages was analyzed through high-throughput sequencing. Results showed that multistage A-O activated sludge process positively influenced polyformaldehyde wastewater. The removal rates of formaldehyde were basically stable at more than 99% and those of COD were about 89%. Analysis of the microbial diversity index indicated that the microbial diversity of the reactor was high, and the treatment effect was good. Moreover, microbial community had certain similarity in the same system. Microbial communities in different units also showed typical representative characteristics affected by working conditions and influent concentrations. Proteobacteria, Firmicutes, and Bacteroidetes were the dominant fungal genera in the phylum level of community composition. As to family and genus levels, Peptostreptococcaceae was distributed at various stages and the dominant in this system. This bacterium also played an important role in organic matter removal, particularly decomposition of the acidified middle metabolites. In addition, Rhodobacteraceae and Rhodocyclaceae were the formaldehyde-degrading bacteria found in the reactor.